Application Of The Cooperative Learning Model In PPKN Learning To Increase Student Motivation - Thomy Sastra Atmaja (Jurnal Scientia, 2024)
This study discusses the application of the cooperative learning model in the subjects of Pancasila and Civic Education (PPKN) and its impact on student learning motivation. The cooperative learning model engages students in small groups to work together to understand the subject matter, building social skills, and increasing engagement in the learning process. The results showed that this model had a significant positive impact on student learning motivation. Students who engage in cooperative learning show increased engagement, a sense of ownership of learning, and confidence. In addition, this model also helps students understand the values of citizenship, cooperation, and social responsibility in the context of globalization. By creating a dynamic, inclusive, and meaningful learning environment, cooperative learning models not only improve academic outcomes but also support students' personal and civic development. This study concludes that the application of the cooperative learning model in PPKN is an effective strategy to increase student motivation and engagement, as well as build important social skills in daily life. Therefore, it is recommended that educators consider the use of this model in the learning process to achieve more optimal results.